(untitled) (Vietnam Journal of Community Medicine, 2025)
Background: One of the essential goals in the care and treatment of patients with chronic obstructive pulmonary disease is to preserve and improve the patient’s quality of life.Objective: Analyze some related factors to the quality of life among outpatients with chronic obstructive pulmonary disease at the Ha Noi Lung Hospital in 2020-2021.Methods: Cross-sectional study. The study collected information from 234 outpatients with chronic obstructive pulmonary disease at the Ha Noi Lung Hospital through by the Saint George respiratory symptom assessment questionnaire for patients with COPD (SGRQ-C). The outpatient’s quality of life was evaluated according to 3 functionals as symptoms, activities, impacts. Factors related to the patient’s quality of life included: Patient’s characteristics, clinical characteristics and support from family and society. Data were entered by Epidata 3.1 and analyzed by SPSS 18.0.Results: The finding showed that, QoL of outpatients was 46.2±17.8. Three factors that have a great impact on the change of quality of life of patients with COPD are family care, psychological support of health workers and level of airway obstruction.Conclusion: The quality of life of outpatients with COPD was average compared with the findings of previous studies. Medical facilities and families need to support patients to adhere to treatment, exercise, and ensure nutrition to improve quality of life for patients.